2022
DOI: 10.1007/s13760-022-01899-z
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in patients with COVID‑19

Abstract: Purpose Autonomic dysfunction in patients with viral infections has been described before. In this study, we aimed to evaluate autonomic functions in patients with the coronavirus infectious disease 2019 . Methods In this cross-sectional study, we compared 112 patients who had recovered from COVID-19 and 106 healthy controls. Symptoms of autonomic dysfunction were assessed with the SCOPA-AUT scale. Results Pupillomotor, urinary and sudomotor subscores of SCOPA-AUT scale were significantly higher in the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, our results found differences considering the non-linear analysis and rating of perceived exertion, and only the age group of 61-80 years presented greater sympathetic activity, worse global variability, and parasympathetic activity considering the indices (indices %1 V, %2 LV, %0 V), and a greater rating of perceived exertion, during the VR activity. These results can be supported by Erdal et al [67] who studied post-COVID autonomic dysfunction, and reported that symptoms of autonomic dysfunction are very common in the post-infectious period of COVID-19 and were associated with age. The most common symptom in the acute phase was fatigue and its presence increased the risk of autonomic dysfunction by 2.2 times in the post-COVID period, but was only evident in older patients.…”
Section: Comparison Of Hrv Between Groups and Different Agessupporting
confidence: 62%
“…However, our results found differences considering the non-linear analysis and rating of perceived exertion, and only the age group of 61-80 years presented greater sympathetic activity, worse global variability, and parasympathetic activity considering the indices (indices %1 V, %2 LV, %0 V), and a greater rating of perceived exertion, during the VR activity. These results can be supported by Erdal et al [67] who studied post-COVID autonomic dysfunction, and reported that symptoms of autonomic dysfunction are very common in the post-infectious period of COVID-19 and were associated with age. The most common symptom in the acute phase was fatigue and its presence increased the risk of autonomic dysfunction by 2.2 times in the post-COVID period, but was only evident in older patients.…”
Section: Comparison Of Hrv Between Groups and Different Agessupporting
confidence: 62%
“…Table 3 displays some studies that examine how frequently COVID-19 patients experience gastrointestinal symptoms. One such study by Erdal et al [ 57 ] found that 21.8% of their 112 COVID-19 patients experienced diarrhea. Another study by Varma-Doyle et al [ 58 ] noted that five of six patients with dysautonomia experienced gastrointestinal symptoms such as bloating, nausea, vomiting, constipation, irregular bowel movements, and early satiety.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is scored from 0 (never) to 3 (often happening), with higher scores indicating more severe dysfunction[ 102 , 103 ]. Researchers have used this scale to evaluate autonomic dysfunction in patients with COVID-19 and found that many patients might have persistent symptoms of autonomic nervous system dysfunction following the acute phase of COVID-19 that might deteriorate and impair clinical recovery[ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrimination value and reliability of the clinical signs and the scores for assessing dysautonomia are limited in critically ill patient are limited. In contrast, pupillometry is simple and validated methods for investigating the ANS dysfunction of the ANS in ICU patients ( Erdal et al, 2022 ; Lai et al, 2020 ; Weise et al, 2022 ). The iris muscle is indeed innervated by the sympathetic and parasympathetic systems, which induce pupillary dilatation and contraction, respectively.…”
Section: Discussionmentioning
confidence: 99%